Bilirubin and Redox Stress in Age-Related Brain Diseases - John Paul Llido; Sri Jayanti; Claudio Tiribelli; Silvia Gazzin (Antioxidants, 2023)
Cellular redox status has a crucial role in brain physiology, as well as in pathologic conditions. Physiologic senescence, by dysregulating cellular redox homeostasis and decreasing antioxidant defenses, enhances the central nervous system’s susceptibility to diseases. The reduction of free radical accumulation through lifestyle changes, and the supplementation of antioxidants as a prophylactic and therapeutic approach to increase brain health, are strongly suggested. Bilirubin is a powerful endogenous antioxidant, with more and more recognized roles as a biomarker of disease resistance, a predictor of all-cause mortality, and a molecule that may promote health in adults. The alteration of the expression and activity of the enzymes involved in bilirubin production, as well as an altered blood bilirubin level, are often reported in neurologic conditions and neurodegenerative diseases (together denoted NCDs) in aging. These changes may predict or contribute both positively and negatively to the diseases. Understanding the role of bilirubin in the onset and progression of NCDs will be functional to consider the benefits vs. the drawbacks and to hypothesize the best strategies for its manipulation for therapeutic purposes.